KEEFEKTIFAN LAYANAN BIMBINGAN KLASIKAL DALAM MENINGKATKAN PEMAHAMAN TERHADAP TINDAKAN PERUNDUNGAN PADA SISWA DI SMP NEGERI 3 ENTIKONG - Anis Syahrul; Halida; Elli Yanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine the effectiveness of classical guidance services assisted by audiovisual media in improving students’ understanding of bullying behavior at SMP Negeri 3 Entikong. The research employed an experimental method with a true experimental design using a posttest-only control design. The sample consisted of 40 students selected through a simple random sampling technique and divided into an experimental group and a control group, each consisting of 20 students. The experimental group received classical guidance services using audiovisual media, while the control group received conventional classical guidance services. Data were analyzed using the Independent Sample ttest with the assistance of SPSS version 22. The results showed that the mean score of the experimental group was 139.5, which was higher than the control group’s mean score of 120.05. The Sig. (2-tailed) value of 0.000 < 0.05 indicated a significant difference between the two groups. Therefore, it can be concluded that classical guidance services assisted by audiovisual media are effective in improving students’ understanding of bullying behavior at SMP Negeri 3 Entikong.